2016
DOI: 10.1161/jaha.116.003426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Statin Therapy on Clinical Outcome in Patients With Coronary Spasm

Abstract: BackgroundStatin therapy reduces the risk of cardiovascular events in patients with obstructive coronary artery disease. The aim of the present study was to determine the effects of statins on the prognosis of patients with coronary vasospastic angina (VSA) free of significant atherosclerotic stenosis.Methods and ResultsAfter exclusion of 475 from 1877 consecutive patients who underwent an acetylcholine‐provocation test between January 1991 and December 2010, data of 640 VSA patients without significant organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 37 publications
2
39
0
1
Order By: Relevance
“…One case had 70% restenosis in stents, two cases had 30% restenosis in stents and the other stents had good adherence and no obvious restenosis. The effective rate of CCB in VA patients in Japan was 92.5% [16] which is similar to our stenting group (88%)and stent-free group(89%) Other literatures reported that aspirin, statins and ACEi could prevent spasm and improve the prognosis of patients [17][18][19] . In addition, we included VA patients,whose diagnostic criteria included resting angina and transient elevation of ST segment one ECG without spasm provocation test, but could be diagnosed as VA with high specificity [10,20,21] , it has been reported that provocation test is safe and effective for VA patients with no significant stenosis [22] ,but provocation test has more advantages than disadvantages for VA patients with severe stenosis [23] , We believe that provocation test may lead to unstable plaque shedding, which increases the incidence of MACE and affects the results of the trial.…”
Section: Discussionsupporting
confidence: 86%
“…One case had 70% restenosis in stents, two cases had 30% restenosis in stents and the other stents had good adherence and no obvious restenosis. The effective rate of CCB in VA patients in Japan was 92.5% [16] which is similar to our stenting group (88%)and stent-free group(89%) Other literatures reported that aspirin, statins and ACEi could prevent spasm and improve the prognosis of patients [17][18][19] . In addition, we included VA patients,whose diagnostic criteria included resting angina and transient elevation of ST segment one ECG without spasm provocation test, but could be diagnosed as VA with high specificity [10,20,21] , it has been reported that provocation test is safe and effective for VA patients with no significant stenosis [22] ,but provocation test has more advantages than disadvantages for VA patients with severe stenosis [23] , We believe that provocation test may lead to unstable plaque shedding, which increases the incidence of MACE and affects the results of the trial.…”
Section: Discussionsupporting
confidence: 86%
“…значительно ограничивало СКА, индуцированного АХ, у пациентов с ВС без обструктивного поражения КА [22]. В более позднем ретроспективном исследовании подтверждалось, что прием статинов подавляет СКА и улучшает прогноз ВС [44]. В настоящее время известно недостаточно данных, характеризующих эффективность антагонистов альфа-1-адренергических рецепторов для лечения ВС.…”
Section: клинико-диагностические алгоритмы и фармакотерапия всunclassified
“…Extensive trials have demonstrated that nitrates are an effective treatment for reducing the frequency of angina in patients with VSA. Studies looked at statin drugs in conjunction with CCBs in preventing coronary artery vasospasm and found that the addition of fluvastatin to CCBs for six months significantly reduced acetylcholine-provoked spasm in patients with VSA without obstructive coronary artery disease [16][17]. There was a correlation between starting statin drug therapy and reduced long-term cardiovascular events in patients with VSA without obstructive coronary artery disease.…”
Section: Managementmentioning
confidence: 99%